Emerging therapies for the treatment of relapsed or refractory multiple myeloma - Dimopoulos, M.A.; San-Miguel, J.F.; Anderson, K.C. (European Journal of Haematology, 2011)
Encouraging progress has been made in the treatment of patients with relapsed/refractory multiple myeloma (MM). The rapidly evolving understanding of key pathways responsible for tumor growth and survival has led to the development of novel agents (including immunomodulatory drugs, proteasome inhibitors, histone deacetylase inhibitors, and other targeted agents) with the potential to provide significant improvements in response and survival, and influence treatment guidelines. This review summarizes recent advances in understanding of the biology of relapsed/refractory MM and clinical trials with novel targeted agents that are currently under investigation for patients with this disease. © 2010 John Wiley & Sons A/S.
Keywords: Akt inhibitor; Histone deacetylase inhibitor; Immunomodulatory drug; multiple myeloma; proteasome inhibitor